Evaluation and Modelling of the Coastal Geomorphological Changes of Deception Island since the 1970 Eruption and Its Involvement in Research Activity - Cristina Torrecillas; Carmen Zarzuelo; Jorge de la Fuente; Bismarck Jigena-Antelo; Gonçalo Prates (Remote Sensing, 2024)
Deception Island is an active volcano with a submerged caldera open to the sea called Port Foster. Several post-caldera-collapsed volcanic events, as well as hydrodynamics, have changed its inner coastline, shaping new volcanic deposits. A hydrodynamic model is presented to predict accretion and erosion trends in this bay, which could have an impact on the mobility of researchers and tourists. New historical orthophotos and spatio-temporal differences between digital elevation and bathymetric models were used for validation purposes. The model reveals that the south-facing coast is more susceptible to erosion, while the east- or west-facing coast experiences sedimentation. A visual study for the periods 1970–2003 and 2003–2020 in Port Foster obtained similar annual erosion/accretion lineal rates (0.3–2 m/year) in the areas not affected by the last eruptive period, as well as increases of 0.023 km2/year and 0.028 km2/year of the inner bay and coastal sedimentation rates of 0.007 km2/year and 0.002 km2/year, respectively. Only part of the significant total volume loss is received within the bay, including its own erosion, and accumulates on the bay bottom. This is largely because the volume input is composed of snow, and it is also due to the transfer of material outside to balance the figures.